US patent no. 6,981,424 B2: Correcting for two-phase flow in a digital flowmeter - Henry, M; de la Fuente, M (United States Patent and Trademark Office, 2006)
A flowmeter is disclosed. The flowmeter includes a vibratable conduit, and a driver connected to the conduit that is operable to impart motion to the conduit. A sensor is connected to the conduit and is operable to sense the motion of the conduit and generate a sensor signal. A controller is connected to receive the sensor signal. The controller is operable to detect a single-phase flow condition and process the sensor signal using a first process during the single-phase flow condition to generate a validated mass-flow measurement. The controller is also operable to detect a two-phase flow condition and process the sensor signal using a second process during the two-phase flow condition to generate the validated mass-flow measurement.